Omics Insight on Fusarium Head Blight of Wheat for Translational Research Perspective - Teli, Basavaraj (Curr Genomics, 2020)
In the scenario of global warming and climate change, an outbreak of new pests and pathogens has become a serious concern owing to the rapid emergence of arms races, their epidemic infection, and the ability to break down host resistance, etc. Fusarium head blight (FHB) is one such evidence that depredates major cereals throughout the world. The symptomatological perplexity and aetiological complexity make this disease very severe, engendering significant losses in the yield. Apart from qualitative and quantitative losses, mycotoxin production solemnly deteriorates the grain quality in addition to life endangerment of humans and animals after consumption of toxified grains above the permissible limit. To minimize this risk, we must be very strategic in designing sustainable management practices constituting cultural, biological, chemical, and host resistance approaches. Even though genetic resistance is the most effective and environmentally safe strategy, a huge genetic variation and unstable resistance response limit the holistic deployment of resistance genes in FHB management. Thus, the focus must shift towards the editing of susceptible (S) host proteins that are soft targets of newly evolving effector molecules, which ultimately could be exploited to repress the disease development process. Hence, we must understand the pathological, biochemical, and molecular insight of disease development in a nutshell. In the present time, the availability of functional genomics, proteomics, and metabolomics information on host-pathogen interaction in FHB have constructed various networks which helped in understanding the pathogenesis and coherent host response(s). So now translation of this information for designing of host defense in the form of desirable resistant variety/genotype is the next step. The insights collected and presented in this review will be aiding in the understanding of the disease and apprise a solution to the multi-faceted problems which are related to FHB resistance in wheat and other cereals to ensure global food safety and food security.